The Impact of Influencer Marketing on Brand Awareness, Customer Brand Engagement, and Overall Brand Quality: Evidence from Optimum Gym Yogyakarta - Aziz Ikko Wanaden Mantofani; Alldila Nadhira Ayu Setyaning (PT FORMOSA CENDEKIA GLOBAL, 2026)
The objective of this study is to investigate the impact of influencer marketing on brand awareness, customer brand engagement, and overall brand quality in the fitness industry, particularly at Optimum Gym Yogyakarta. The increase in competition in the fitness industry as well as the shift toward digital marketing strategies using influencers, as applied by Optimum Gym using the fitness influencer